2012
DOI: 10.1186/1824-7288-38-53
|View full text |Cite
|
Sign up to set email alerts
|

I-131-Metaiodobenzylguanidine therapy with allogeneic cord blood stem cell transplantation for recurrent neuroblastoma

Abstract: Iodine-131-metaiodiobenzylguanidine (131I-MIBG) therapy combined with allogeneic cord blood stem cell transplantation (SCT) was used to treat a 4-year-old girl with recurrent neuroblastoma. The patient experienced relapse 2 years after receiving first-line therapies, which included chemotherapy, surgical resection, irradiation, and autologous peripheral SCT. Although 131I-MIBG treatment did not achieve complete remission, the size of the tumor was reduced after treatment. Based on our findings, we suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Conversely, Goi et al . reported successful tandem autologous‐cord blood SCT in three patients with advanced neuroblastoma with amplified MYCN , whereas MIBG therapy with myeloablative CBT to recurrent neuroblastoma was described . Although several reports suggested that cord blood includes anti‐tumor effector cells against neuroblastoma, those reports did not elaborate on KIR‐ligand mismatches …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Goi et al . reported successful tandem autologous‐cord blood SCT in three patients with advanced neuroblastoma with amplified MYCN , whereas MIBG therapy with myeloablative CBT to recurrent neuroblastoma was described . Although several reports suggested that cord blood includes anti‐tumor effector cells against neuroblastoma, those reports did not elaborate on KIR‐ligand mismatches …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Goi et al 24 reported successful tandem autologous-cord blood SCT in three patients with advanced neuroblastoma with amplified MYCN, whereas MIBG therapy with myeloablative CBT to recurrent neuroblastoma was described. 25 Although several reports suggested that cord blood includes anti-tumor effector cells against neuroblastoma, those reports did not elaborate on KIR-ligand mismatches. 26 Natural killer cells express inhibitory KIR on the cell surface, and NK cell alloreactivity in the setting of allogeneic transplantation is determined by the specificity of KIR on donor NK cells for the recipient major histocompatibility complex (MHC) class I.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have recently reported the possibility to induce a graft-versus-tumor (GVT) effect against advanced neuroblastoma [ 55 57 ]. Two patients with relapsed neuroblastoma treated with I-131 MIBG and allo-HCT were reported in case reports from Japan [ 58 , 59 ]. A 6-year-old female with relapsed neuroblastoma received reduced-intensity allo-HCT 21 days after I-131 MIBG therapy [ 59 ].…”
Section: I-131 Mibg Therapy and Allogeneic Stem Cell Transplantatimentioning
confidence: 99%
“…Though no GVT effect was observed, the patient was in CR for 3 months after allo-HCT. A 5-year-old female with relapsed neuroblastoma was executed cord blood stem cell transplantation (CBSCT) 9 days after I-131 MIBG therapy and GVT effect was observed after CBSCT [ 58 ]. Normalization of both vanillylmandelic acid and homovanillic acid for 5 months and decrease of I-123 MIBG accumulations were maintained, although the patient died 12 months after CBSCT.…”
Section: I-131 Mibg Therapy and Allogeneic Stem Cell Transplantatimentioning
confidence: 99%